2023
DOI: 10.1002/advs.202304140
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Printed Electronic Textiles

Md Rashedul Islam,
Shaila Afroj,
Junyi Yin
et al.

Abstract: Electronic textiles (e‐textiles) have emerged as a revolutionary solution for personalized healthcare, enabling the continuous collection and communication of diverse physiological parameters when seamlessly integrated with the human body. Among various methods employed to create wearable e‐textiles, printing offers unparalleled flexibility and comfort, seamlessly integrating wearables into garments. This has spurred growing research interest in printed e‐textiles, due to their vast design versatility, materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 531 publications
0
6
0
Order By: Relevance
“…[36][37][38] An abundant selection of wearable respiratory devices currently exists for measuring both mechanical and chemical respiratory information. [39][40][41][42] Wearable respiration devices show several advantages over their stationary counterparts which are commonly used in hospitals. [43][44][45][46] The most basic test, spirometry, to assessments using significantly more complicated machinery like plethysmography, all suffer from an inability to acquire consistent respiratory information.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[36][37][38] An abundant selection of wearable respiratory devices currently exists for measuring both mechanical and chemical respiratory information. [39][40][41][42] Wearable respiration devices show several advantages over their stationary counterparts which are commonly used in hospitals. [43][44][45][46] The most basic test, spirometry, to assessments using significantly more complicated machinery like plethysmography, all suffer from an inability to acquire consistent respiratory information.…”
Section: Introductionmentioning
confidence: 99%
“…An abundant selection of wearable respiratory devices currently exists for measuring both mechanical and chemical respiratory information 39–42 . Wearable respiration devices show several advantages over their stationary counterparts which are commonly used in hospitals 43–46 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, conductive inks are widely used for the fabrication of a broad range of devices for specialized applications, from sensors, integrated circuits, wearable electronics, radiofrequency identification tags, to energy harvesting/storage systems [9,10,[13][14][15][16][17][18][19]. For example, Barmpakos et al [9,10] showed that commercial graphene and f -rGO [6] can perfectly act as temperature sensors as well as heaters with a stable response and durability to thermal stressing for ink-jet printed devices.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 These textiles, fabricated into wearable sensors, enable real-time, continuous monitoring of critical health parameters such as brainwave and muscle activity, temperature, biophotons, and specific biomarkers in sweat or breath, which is vital for managing abnormal physiological states. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Additionally, textile-based lab-on-chip systems have been developed, integrating microfluidics for immediate, on-site analysis of biomarkers using minute biofluid samples, including sweat, saliva, or blood. 22 , 23 In wound care, intelligent bandages and biosensor-equipped dressings are transformative, enabling monitoring of healing and infection detection without the need for dressing removal, thus promoting personalized medical care.…”
Section: Introductionmentioning
confidence: 99%